2009
DOI: 10.1161/strokeaha.108.532085
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Are Major Players in the Prognosis and Risk of Infection After Acute Stroke

Abstract: Background and Purpose-Monocytes participate in adaptive and innate immune responses. Monocyte numbers increase in patients with stroke associated infection (SAI) or severe stroke. Whether changes in monocytes are related to specific effects, or simply mark brain damage, remains unsettled. Methods-We used flow cytometry in 45 consecutive strokes and 12 healthy controls to assess the time course of monocytes, their phenotype, and the production of cytokines after stimulation. Cortisol, TNF-␣, IFN-␥, and IL-10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
157
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 44 publications
23
157
3
4
Order By: Relevance
“…Compared with controls, the total number of monocytes was similar in patients on admission and at day 90, but higher at day 2 and at day 7 (Figure 2A), as reported earlier (Urra et al, 2009a). Furthermore, the proportion of CD14 high CD16À monocytes did not change significantly after stroke, but there was a 38% relative increase in CD14 high CD16 + monocytes and a 41% relative decrease in CD14 dim CD16 + monocytes.…”
Section: Monocyte Subtypes and Phenotypesupporting
confidence: 82%
See 2 more Smart Citations
“…Compared with controls, the total number of monocytes was similar in patients on admission and at day 90, but higher at day 2 and at day 7 (Figure 2A), as reported earlier (Urra et al, 2009a). Furthermore, the proportion of CD14 high CD16À monocytes did not change significantly after stroke, but there was a 38% relative increase in CD14 high CD16 + monocytes and a 41% relative decrease in CD14 dim CD16 + monocytes.…”
Section: Monocyte Subtypes and Phenotypesupporting
confidence: 82%
“…Earlier studies have shown that poor outcome after stroke is associated with innate responses signaled through TLR4 in monocytes (Urra et al, 2009a;Yang et al, 2008). In this study, the expression of TLR4 disclosed no significant differences between monocyte subtypes, suggesting that other differences in monocyte subtypes affect stroke outcome.…”
Section: Figurecontrasting
confidence: 44%
See 1 more Smart Citation
“…As would be expected, the peripheral systemic inflammatory response, evidenced by plasma CRP concentrations and peripheral white-blood counts, is exaggerated in patients with infection, compared to those without (Emsley et al 2003;Fassbender et al 1997). In contrast to the elevated plasma concentrations of inflammatory markers in acute concentrations in the acute phase were associated with stroke-associated infections independent of stroke severity and age (Urra et al 2009). However, in another study, induction of TNF and monocytic HLA-DR expression were associated with incident infections, but these relationships were not independent of infarct volume (Hug et al 2009).…”
Section: Inflammation and Outcome Following Ischemic Strokementioning
confidence: 92%
“…The number of monocytes is elevated in patients with severe stroke or stroke associated infection. Stroke associated infection may result from the immunosuppressive and anti-inflammatory effects of corticoids, catecholamines, IL-10 and deactivated monocytes [24]. IL-1β expression by HIV infected cells may be one of the important factors for induction of HIV encephalitis.…”
mentioning
confidence: 99%